Taking charge of professional development : a practical model for your school - Semadeni, Joseph H. (ASCD, 2009)
Learn how to overcome budget cuts, lack of leadership, top-down mandates, and other obstacles to professional development. Topics include how to combine time, a motivational system, and teacher leadership to generate a schoolwide improvement effort.